Menumbuhkan Karakter Keadilan Anak Usia Dini melalui Permainan Tradisional Nusantara (Fokus: Pengembangan Buku Pedoman Pendidikan Karakter) - Rahmawati, Helena Twindi; Nugrahanta, Gregorius Ari (Cokroaminoto Journal of Primary Education, 2024)
The prevalence of justice character crisis in children is the main problem in this study. Developing a guidebook of traditional games to foster the character of justice in children aged 7-9 years is the purpose of this research. In this study, the method used was ADDIE-type Research and Development (R&D). Researchers involved ten teachers, ten validators, and eight children aged 7-9 years in the implementation of this study. The results showed that, 1) the product in the form of a justice character guidebook was developed with ADDIE steps, 2) the quality of the research product obtained an average score of 3.71 which fell into the "Very good" category with the recommendation "No need for revision". 3) the application of the research product has an influence on the character of justice in children aged 7-9 years. Significance test with paired samples t test shows the mean score of posttest (M = 3.5000, SE = 0.05976) is higher than the mean of pretest (M = 2.1250, SE = 0.14485) and the value of t(7) = 9.259, p = 0.000 (p < 0.05), then Hnull is rejected. The effect size is r = 0.961 which is classified as "Large effect" with a percentage of 92.45%. The result of N-gain score analysis is 72.63% which is categorized in "High" effectiveness. Thus, the traditional game guidebook is effective in fostering the character of justice in children aged 7-9 years.